Peran Orang Tua dalam Pemantauan Tumbuh Kembang Anak Usia Dini - Meymi Putri, Anggun; Nadya, Khoirun; Amanda, Putri; Khadijah, Khadijah; Nasution, Homsani (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2025)
This study aims to describe the role of parents in monitoring the growth and development of early childhood children and the forms of monitoring conducted at home. The study used a qualitative descriptive approach through in-depth interviews with five parents of children aged 4–5 years in Medan Denai District. The results indicate that parents play a role in three main ways: observing their children's development at home, providing stimulation as needed, and utilizing health services such as integrated health posts (Posyandu). Monitoring is carried out on speaking, walking, playing, and physical growth, while stimulation is provided through play, reading, chatting, and drawing. However, monitoring is not comprehensive because parents tend to focus on physical aspects, while social-emotional development, independence, and cognitive development are less considered. The use of Posyandu is also limited to physical examinations, resulting in incomplete information on children's development. These findings provide theoretical contributions to the study of Early Childhood Education and parenting, particularly in strengthening the concept of family involvement in monitoring child development. Practically, the results of this study can form the basis for developing parent education programs and collaboration with health workers for more comprehensive monitoring. The study recommends improving parents' understanding of development indicators through ongoing education and support from health workers so that child growth and development monitoring can be carried out optimally